Blue economy and food security the way forward: A systematic literature review analysis - Sardan, Mohd Azim; Ali, Norfariza Mohd; Ali, Azman; Samsudin, Aidarohani; Harun, Nurul Fahana Aini; Tan, Yan-Ling; Kadir , Juliana Mohamed Abdul (International Journal of Asian Social Science, 2023)
Sustainable growth spotlights the significant challenges of the blue economy and food security. Escalating global attention has fueled fresh scientific inquiry into these areas, driven by their paramount importance in addressing pressing issues. This paper explores into the intersection of these concerns, which particularly emphasizing the supply chains of ocean resources, which have gained prominence due to the escalating effects of climate change. The changing climate exacerbates the vulnerabilities of oceanic food sources, compounding the urgency of understanding this nexus. To illuminate this complex landscape, the paper employs a comprehensive approach, encompassing a systematic literature review spanning seven years, 2017 and 2023. A dataset of 28 research papers sourced from the Scopus and WoS databases provides the foundation for this analysis. Through content analysis, thematic areas are identified, allowing for the identification of key trends and concerns within the literature. The results of this study extend beyond mere data trends; they encompass geographical distributions and reveal three overarching themes that encapsulate the study’s focal areas: the blue economy, food security, and ocean governance. In essence, this research contributes to a deeper comprehension of the intricate interplay between the blue economy and food security, shedding light on the multifaceted challenges that must be tackled to achieve sustainable growth in the face of evolving climate dynamics and increasing global demands.